Copper-catalyzed regioselective sulfonylcyanations of vinylarenes. Issue 15 (30th June 2020) - Liu, Lei; Si, Mingran; Han, Shengnan; Zhang, Yan; Li, Jie
Abstract : A set of copper-catalyzed sulfonylcyanations of vinylarenes with readily accessible arylsulfonyl chlorides and trimethyl cyanide was achieved, providing a streamlined route to various decorated β-sulfonyl nitriles with good regioselectivity and functional group tolerance. Abstract : A set of copper-catalyzed sulfonylcyanations of vinylarenes with readily accessible arylsulfonyl chlorides and trimethyl cyanide was accomplished under mild conditions, thus providing a step-economic streamlined route to various decorated β-sulfonyl nitriles with good regioselectivity and functional group tolerance. Preliminary mechanistic studies suggested that this type of reaction undergoes a classic radical chain process.